ChemInform Abstract: Gold‐Catalyzed Cycloisomerization and Diels—Alder Reaction of 1, 6‐Diyne Esters with Alkenes and Diazenes to Hydronaphthalenes and ‐cinnolines. Issue 4 (January 2016) - Yan, Jianming; Tay, Guan Liang; Neo, Cuien; Lee, Bo Ra; Chan, Philip Wai Hong
Abstract: The one‐pot title process between 1, 6‐diyne esters and electron‐deficient dienophiles such as maleic acid derivatives, tetracyanoethene, benzoquinone, and azodicarboxylates is described.